Aplicación SIG (Sistema de Información Geográfico) para la caracterización y análisis hidrológico de la cuenca superior del río Zamora (Hoya de Loja). - Ludeña Castillo, Hernán Sígel (2008)
Currently the advancement of technology with regard to the management of Geographic Information Systems, has highlighted the creation of new initiatives aimed at the development of GIS applications in free environment, purporting to be a viable alternative to commercial programs. However the main idea is not to compete with large existing solutions in the market; but it is perceptible as this led to cost is a primary agent in small local institutions, educational and research centers, small businesses, etc., and the high level of training is needed; GIS's free tools are being presented as the best option. As also shown in our city this factor and trying to solve, in a way, with feasible aid to society, it was considered aim to develop a GIS application for characterization and hydrological analysis of the Upper River Basin Zamora in Hoya Loja supported by the Integrated Environmental Geomatics Center for purposes of planning for decision-making professionals involved in the hydrological field For application development work was done on one of the free GIS tools for desktop, as is MapWindow which has a OCX component for IT developers that allows programming to user needs using the C # language of the Visual Studio platform. Net. As well as storing important data for hydrological analysis in a solvent-based data like MySql.